Arts and Crafts Activities and Their Impacts on Teaching and Learning: A Case Study of Social Studies Department - Jaksan, Rapeepan; Potjanalawan, Pinyapan (Thai Journal of East Asian Studies, 2019)
This article aims to describe the change in the students’ arts and crafts fair which has affected to the education in Department of Social Studies in the school. The fair has its long history. It used to be the activities in the center of country at the capital and were set in the regions later in the 1990s. These fairs have significantly influenced to schools, teachers and students, such as the effect to classroom hour and budgets. They also made teachers progress in their career path relating to the promotion criteria. However the change of that criteria might change the students’ arts and crafts fairs to a new fade.